Adaptation of Physical Environment in Health Care Institutions for People with Disabilities Caused by Musculoskeletal System and Connective Tissue Disease - Rupšienė, Liudmila; Saveljeva, Regina; Ruškė, Jūratė (Social Welfare: Interdisciplinary Approach, 2024)
The UN World Health Organization has set a goal to ensure people-oriented universal, equal, sustainable and high quality health systems which would give priority to prevention of diseases, continuous perfection of quality, integrated provision of services, assurance of continuous care, development of patients’ self-care, relocation of care close to home by 2020. People with disabilities and their opportunities to equally participate in the health system like other citizens occurred in the high focus because over recent decades various international documents acknowledge that, despite various measures and obligations, people with disabilities face violations of their rights in various spheres of living worldwide. The paper presents the research that aimed at investigating the adaptation of physical environment in health care institutions focused on people with disabilities caused by the disease of the musculoskeletal system and connective tissue. The research suggests that people with disabilities caused by the disease of the musculoskeletal system and connective tissue face a greater burden, and the disability has become an obstacle to their enjoyment of human rights and freedoms in the health system. This testifies to the fact that the Lithuanian state does not guarantee this part of its citizens the same quality of health services as other citizens, as provided for in the United Nations Convention on the Rights of Persons with Disabilities (2006).
Keywords: Healthcare; quality; disability; environment